1999
DOI: 10.1046/j.1537-2995.1999.39070674.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical consequences of alterations in platelet transfusion dose: a prospective, randomized, double‐blind trial

Abstract: As compared to the administration of HDPs, the administration of LDPs for prophylactic transfusion in hematopoietic progenitor cell transplant patients results in a lower platelet count increment, a lower likelihood of obtaining a posttransfusion platelet increment >20,000 per microL, a shorter transfusion-free interval, and a greater relative risk per day of requiring additional transfusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 36 publications
6
78
0
Order By: Relevance
“…30 Importantly, the responses to test and reference platelet concentrates were comparable over the range of platelet doses used in clinical practice, and average test and reference 1-and 24-hour count increment and CCI were within previously reported ranges for similar patient populations. 16,17,26 In comparison with other recent studies examining the effect of platelet dose on the interval to the next transfusion, 17,29 test platelets in the present study demonstrated transfusion intervals within reported ranges.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…30 Importantly, the responses to test and reference platelet concentrates were comparable over the range of platelet doses used in clinical practice, and average test and reference 1-and 24-hour count increment and CCI were within previously reported ranges for similar patient populations. 16,17,26 In comparison with other recent studies examining the effect of platelet dose on the interval to the next transfusion, 17,29 test platelets in the present study demonstrated transfusion intervals within reported ranges.…”
Section: Discussionsupporting
confidence: 61%
“…Both test and reference platelet count increments were within reported therapeutic ranges. 16,17 When the 1-hour count increment was adjusted for differences in platelet dose using the CCI, the mean 1-hour CCI was not statistically significantly different between treatment groups (13 100 Ϯ 5400 vs 14 900 Ϯ 6200, P ϭ .11), with a mean difference of 1800 (95% CI, Ϫ400 to 4100). By longitudinal regression analysis for all transfusions, platelet concentrates prepared with and without PCT did not differ significantly with respect to the 1-hour posttransfusion platelet count in cycle 1 (P ϭ .53).…”
Section: Platelet Count Increments 1 Hour After Transfusionmentioning
confidence: 98%
“…The use of SDAP or higher doses of platelets is still controversial and associated with higher costs. 14,15 Some authors advocate the use of SDAP due to less exposure to multiple donors, resulting in smaller risk of contamination with infectious diseases and lower risk of developing alloantibodies. 16,17 However, it is unclear if using SDAP improves outcomes of transfusions, as opposed to using the more readily available pooled platelet concentrates (PPC).…”
Section: Introductionmentioning
confidence: 99%
“…Only in the late 1990s and early part of the twenty-first century were various studies done to try to establish an optimal prophylactic platelet count threshold for prophylactic platelet transfusions in thrombocytopenic patients. 8,10,11,12,13 The most widely quoted trial, which used a lower prophylactic trigger of 10×10 9 /L versus 20×10 9 /L, was evaluated in a multicenter, randomized clinical trial (RCT). 10 This group studied adult patients receiving induction therapy for newly diagnosed AML.…”
Section: Prophylactic Platelet Transfusionsmentioning
confidence: 99%